Teaching and learning of electric charge with PIMCA model - Nasra, F; Mongan, SW; Nusa, J; Poluakan, C; Mondolang, AH; Lolowang, J (Journal of physics. Conference series, 2021)
Research on the physics learning of electric charge has been carried out using MR-SR (Multiple Representation and Semiotic Resources). The research aims to find out the outcomes of student learning using the PIMCA learning model (Presentation, Idea Mapping, Conceptualization, and Assessment formative) introduced and developed by Cosmas Poluakan. The research was conducted at the Department of Physics, Manado State University, with 22 pre-service teacher students as respondents using the One Group Pre-test-Post-test Design. The instruments used in the form of pre-test and post-test which have been tested and validated. The research implementation stage starts from the pre-test, and then the implementation of physics learning follows the 4 steps of the PIMCA model. The results of data processing and analysis obtained an average pre-test score is 18,88 and an average post-test score is 75,16. There was an increase in concept mastery. In the idea mapping stage only 2 concepts are correct to drafting concept mapping, 6 are correct from 10 concepts that were used as references. PIMCA MR-SR learning model is very effective in helping students find and understand the correct concepts of physics. The use of the PIMCA MR-SR as a new model in the teaching and learning process is very effective in learning physics, mathematics and science or in the STEM area.